RENEWABLE SOURCES OF ENERGY: MERITS AND DEMERITS - BADHE, S.G.; PATIL, M.R. (Innovare Journal of Sciences, 2020)
Energy demand is continuously increasing. Energy is one of the importantneeds of society. Natural energy resources are materials or things that people use from the earth. Theseenergy sources are divided in renewableand nonrenewableenergy sources. Renewable sources are free and abundant in nature on the other hand nonrenewable sources are limited and also to sustain life on earth. Nonrenewable sources causes pollution and hence degrade the environment.As the nonrenewable sources are limited on the earth the utilization of renewable energy sources has become inevitable. Renewable energy is derived from natural process that can be replenished. Depending on the sources of energy renewable energy sources are derived in various types. This paper deals with the Merits and Demeritsof renewable and nonrenewable energy sources.